Strategi Pemasaran dalam Meningkatkan Daya Tarik Pelanggan : Studi Kasus Koperasi Induk Puteri Nurul Jadid (Wil. Az- Zainiyah) - Juaedi, Dedy; Nafi’ah, Alisa Hidayatun; Wulandari, Ayu Widia; Aisyah, Dita; Fitriya, Lailatul; Rohmah, Siri Nurul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the marketing strategies of the Puteri Nurul Jadid Cooperative in the Az-Zainiyah region to increase customer appeal. Using descriptive qualitative methods through observation, interviews, and documentation, the study found that the cooperative has implemented effective marketing strategies in the form of neat and systematic store layout, discount programs for products nearing expiration, and friendly service. These strategies have proven to increase shopping interest and customer loyalty, especially among students. However, there are still challenges such as a lack of training for employees and customers' lack of discipline in maintaining store tidiness. The study recommends the development of human resource training programs and the strengthening of member loyalty programs to optimize the cooperative's marketing strategies.